Using ODD for HTML - Martin Holmes (Journal of the Text Encoding Initiative)
Although the ODD (One Document Does it all) language is normally used to create TEI customizations or extensions, it is also a highly effective tool for editors working in other XML markup languages. This paper will discuss the use of ODD to define a highly constrained schema for HTML5 that will enforce stylistic rules and encoding practices, define custom attributes and value lists, and enable easier editing and validation of project content in the Oxygen XML Editor environment. I will provide a brief history of the project, whose first incarnation, created with the Dreamweaver HTML editor, was somewhat chaotically coded, and show how the implementation of an ODD-based schema provides huge advantages for authors, editors, and encoders, as well as substantially simplifying the code itself.